The Effect of Environmental Enrichment on Selected Physiological and Immunological Stress-Related Markers in Dairy Goats - Yossi Wein; Ofri Vaidenfeld; Chris Sabastian; Enav Bar Shira; Sameer J. Mabjeesh; Haim Tagari; Aharon Friedman (Biology)
Homeostasis preservation is essential for animal survival, and any event that causes a disturbance in homeostasis is defined as a stressor. Here, we aimed to evaluate the effect of scratch brushes and stages as an environmental enrichment to alleviate stress in dairy goats. Twenty-four mixed-breed goats were divided into two groups according to common physiological conditions in breeding farms: milking and dry (milk-producing and non-milk-producing, respectively). Ten days after exposure to environmental enrichment treatment or not (control), blood was sampled. Following the enrichment, we observed a reduction in reactive oxidative stress metabolites, advanced glycation end products (AGEs), and their binding protein (transferrin) in the dry goats, as determined by an ELISA. In contrast, no change in AGEs, along with an increase in transferrin levels, was observed in the milking goats. Moreover, oxytocin levels decreased in the dry and increased in the milking goats, while serotonin levels increased in the dry and remained unchanged in the milking goats. Additionally, gene expression of the cytokines, IL-6 and IL-1ß, and anti-oxidative proteins, lysozyme and transferrin (in peripheral blood leukocytes), as determined by qPCR, presented the same pattern: down-regulation in the dry or up-regulation in the milking goats. In conclusion, a reliable methodology was developed for measuring husbandry stress in goats and to improve dairy goats’ husbandry practice. Current environmental enrichment produced different responsiveness in goats correlated to their physiological status: beneficial effect in dry goats, detrimental effect in milking goats.